On non-surjective coarse isometries between Banach spaces. Issue 3 (16th March 2019) - Cheng, Lixin; Fang, Quanqing; Luo, Sijie; Sun, Longfa
Abstract: Assume that X, Y are real Banach spaces, Y has uniform convexity of type p ( ≥ 1), and f : X → Y is a standard coarse isometry. In this paper, we show that if then there is a linear isometry U : X → Y so that where is defined by Representation properties of coarse isometries in free ultrafilter limits on are also discussed.